Novel, Anti-hTNF-α Variable New Antigen Receptor Formats with Enhanced Neutralizing Potency and Multifunctionality, Generated for Therapeutic Development - Ubah, Obinna C.; Steven, John; Kovaleva, Marina; Ferguson, Laura; Barelle, Charlotte; Porter, Andrew J. R.; Barelle, Caroline J. (Frontiers in Immunology, 2017)
The management of chronic inflammatory diseases such as inflammatory bowel disease (IBD), psoriasis, and rheumatoid arthritis (RA) has significantly improved over the last decade with the clinical availability of anti-TNF-α biologics. Despite this undoubted treatment success, a combination of acquired resistance together with an increased risk of systemic complications, means that a significant number of patients either fail to find a suitable targeted therapy or frustratingly discover that an approach that did work is no longer efficacious. Here we report the isolation and characterisation of a new class of super-neutralising anti-TNF-α biologics formats, the building blocks of which were originally derived as variable new antigen receptor (VNAR) domains from an immunised nurse shark. These parental small, stable VNAR monomers recognise and neutralise TNF-α, in cell-based assays, at nanomolar concentrations. However, the simple, single-chain molecular architecture of VNARs allows for easy and multiple reformatting options. Through reformatting, we achieved a 50,000-fold enhancement in in vitro efficacy with super-neutralising fusion-proteins able to block TNF-α induced cytotoxicity in the 2-5 picomolar range whilst retaining other functionality through the addition of fusion proteins known to extend serum half-life in vivo. In an in vitro intestinal epithelial barrier dysfunction efficacy model, the lead VNAR domains, restored barrier function and prevented paracellular flux with comparable efficacy to adalimumab (Humira®). In addition, all multivalent VNAR constructs restored trans-epithelial electrical resistance (TEER) to approximately 94 % of the untreated control. Reformatted VNAR domains should be considered as a new class of biologic agents for the treatment of hTNF-α driven diseases; either used systemically with appropriate half-life extension or alternatively where site-specific delivery of small and stable neutralisers may provide improvements to current therapy options.